Nematicidal spore-forming Bacilli share similar virulence factors and mechanisms - Zheng, Ziqiang (Sci Rep, 2016)
In the soil environment, Bacilli can affect nematode development, fecundity and survival. However, although many Bacillus species can kill nematodes, the virulence mechanisms Bacilli utilize remain unknown. In this study, we collected 120 strains comprising 30 species across the Bacillaceae and Paenibacillaceae families of the Bacillales order and measured their nematicidal activities in vitro. Comparison of these strains’ nematicidal capacities revealed that nine species, including Bacillus thuringiensis, B. cereus, B. subtilis, B. pumilus, B. firmus, B. toyonensis, Lysinibacillus sphaericus, Brevibacillus laterosporus and B. brevis, were highly nematicidal, the first of which showed the highest activity. Genome sequencing and analysis identified many potential virulence factors, which grouped into five types. At least four possible mechanisms were deduced on the basis of the combination of these factors and the bacterial nematicidal activity, including a pore-forming mechanism of crystal proteins, an inhibition-like mechanism of thuringiensin and a degradation mechanism of proteases and/or chitinases. Our results demonstrate that 120 spore-forming Bacilli across different families share virulence factors that may contribute to their nematicidal capacity.